The Effect of Internal Control, Risk Management, and Whistleblowing Systems on Fraud Prevention - Marseli, Dea; Novitasari, Novitasari (Journal of International Accounting, Taxation and Information Systems, 2025)
This study aims to determine the effects of internal control, risk management, and whistleblowing on fraud prevention. The research sample included as many as 75 respondents, including structural officials within OPD. Quantitative research using the survey approach method was used. The secondary data used were questionnaires distributed to the Lebong district OPD officials. The data analysis method used was multiple linear regression using SPSS version 29. This study results the internal control variable significantly affects fraud prevention, the risk management variable has no significant effect on fraud prevention, and the whistleblowing system variable significantly affects fraud prevention. This study provides practical insights for government organizations to strengthen fraud prevention strategies through better monitoring and reporting mechanisms. In addition, risk management needs to be reviewed to be more effective in reducing potential fraud. By implementing the right strategy, OPD can create a more transparent and accountable financial and operational management environment